CLINICAL AND LABORATORY FEATURES OF ACUTE MESENTERIC ISCHEMIA COURSE - Z. A. Artamonova; E. V. Namokonov (Acta Biomedica Scientifica)
The aim. of our study was to analyze clinical and laboratory features of acute mesenteric ischemia course and to reveal possible ways to improve patients care in this category in non-specialized. multidisciplinary medical institution. The study is based, on the analysis of case histories of patients treated, in the ward of general surgery of Railway Clinical Hospital of Chita in 2007—2011 years with acute mesenteric ischemia as well as the analysis of autopsy protocols of this category of patients. Analysis of clinical records revealed, a number of symptoms, the presence of which in people of group of risk on the acute mesenteric ischemia allows to diagnose and. to start pathogenetic therapy in the first hours of the disease.